(untitled) (Raparin Journal of Humanities (RJH), 2023)
The University is considered an important academic center to prepare students for a better future. University students will face many changes during their studies, which may affecting their overall performance, study and decision-making. Their problems and adaptation mean high cognitive flexibility, as some students cannot adapt to their problems. This study aimed to determine statistical differences in cognitive flexibility among kindergarten students in Kurdistan Regional University. Knowing the different levels of cognitive flexibility statistics among kindergarten students according to university variables (Salahaddin, Sulaimani, Raparen, Halabja , Garmian). The determine statistical differences in cognitive flexibility between first and third- grade students of kindergarten departments in each of the Kurdistan Regional University. the researcher uses a quantitative descriptive method because it is appropriate to the nature of the research. Sample selection The researcher random sampling from the kindergarten department, which consisted of (345) students and they divided into five universities (Salahaddin, Sulaimani, Raparen, Halabja , Garmian), the researcher was able to prepare the measure of cognitive softness using the measure (Al-Mayahi, Razi, 2019), and the researcher used the SPSS program as a method to analyze the data. Results of the study cognitive flexibility among kindergarten students is at a high level, there is a difference in cognitive flexibility according to the university variable, there is no difference in cognitive flexibility between first and third grade students in kindergarten in each of the universities in the Kurdistan Region. Based on the results Obtained by the researcher, the researcher makes some suggestions and recommendations to the places related to the research.